2012
DOI: 10.1007/978-3-642-35341-3_21
|View full text |Cite
|
Sign up to set email alerts
|

What Snippets Say about Pages in Federated Web Search

Abstract: Abstract.What is the likelihood that a Web page is considered relevant to a query, given the relevance assessment of the corresponding snippet? Using a new federated IR test collection that contains search results from over a hundred search engines on the internet, we are able to investigate such research questions from a global perspective. Our test collection covers the main Web search engines like Google, Yahoo!, and Bing, as well as a number of smaller search engines dedicated to multimedia, shopping, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
(15 reference statements)
3
10
0
Order By: Relevance
“…A result (i.e., a filled out form) denotes a set of field-value pairs. On a result level, the agreement of our judgments and those of the participants is 0.33, which is consistent with the "key" agreement reported in (Demeester et al, 2012). Though it might seem low, it is a direct result of the strict comparison: one slightly different field value causes results to disagree completely.…”
Section: Data Obtainedsupporting
confidence: 90%
“…A result (i.e., a filled out form) denotes a set of field-value pairs. On a result level, the agreement of our judgments and those of the participants is 0.33, which is consistent with the "key" agreement reported in (Demeester et al, 2012). Though it might seem low, it is a direct result of the strict comparison: one slightly different field value causes results to disagree completely.…”
Section: Data Obtainedsupporting
confidence: 90%
“…The FWS collection presented in [4] contains several levels of relevance judgments, but here we will only consider strict binary relevance levels, for which snippets were judged to be definitely relevant 3 , and pages were indicated as highly relevant or better. In [3] it was shown that even for the best resources only about 2/3 of all 'definitely relevant' snippets corresponded with a highly relevant result page.…”
Section: Inferring Relevance From Snippetsmentioning
confidence: 99%
“…In [3] it was shown that even for the best resources only about 2/3 of all 'definitely relevant' snippets corresponded with a highly relevant result page. A classifier trained on snippet labels would hence not be able to overcome this intrinsic gap in relevance when used for the prediction of the page labels.…”
Section: Inferring Relevance From Snippetsmentioning
confidence: 99%
See 2 more Smart Citations